Mute Phantoms: a Note on the Painting - Ćipranić, Miloš (Escritura e Imagen, 2019)
Mutism and visuality are two basic elements of the eidetic structure of paintings. In European art theory, from Plato to Ortega y Gasset and Merleau-Ponty, there is an ambivalence in the valuation of these two elementary properties of the pictural work. On the one hand, the painting is underestimated as a visual entity – in front of other forms of expression and communication – because it cannot speak. On the other hand, in its silence a certain space of the visible is acknowledged that verbal language cannot fully encompass. Finally, if visual mutism is a fundamental characteristic of the pictural images, questions arise about how to confirm with certainty what these images mean and how to construct a philosophical discourse on this assumption.
Keywords: painting; mutism; visuality; Plato; Ortega y Gasset; Merleau-Ponty